TEKNIK PENILAIAN GURU DALAM PRAKTIK TARI PADA PEMBELAJARAN SENI BUDAYA DI SMP NEGERI 1 PULAU PUNJUNG KABUPATEN DHARMASRAYA - Anjani, Welly; Yuliasma, Yuliasma (SENDRATASIK UNP, 2019)
Abstract The sudy aims to find out the techniques of learning assessment of dance and the obstacles encountered in designing dance techniques of learning assessment in SMP Negeri 1 Pulau Punjung. This study used desciptive qualitative approach. The research instrument was the researcher and was assisted by supporting instruments such as audio visual stationery and smartphone. Techniques of Data collection were carried out by taking library studies, observations, interviews and documentation. The steps in  analyzing data were collecting, describing  and making data conclusions. The result shows that the assessment techniques that are performed by the cultural arts teacher (Dance) in SMP Negeri 1 Pulau Punjung are performance, product, project, portfolio and practice appraisals. Meanwhile, the obstacles in designing assessment techniques in SMP 1 Pulau Punjung are difficulties in choosing material and determining assessment indicators. So it can be concluded that not all assessments based on the curriculum 2013 can be carried out optimally, because of the limited ability of teacher’s can not be carried out properly because in addition to the constraints of students and the training room, it can also be seen from the limited hours of cultural arts lessons making it difficult for the teacher to implement all assessment techniques. Keywords: teacher assessment techniques, dance practices, cultural arts